Transdiscipline, Historical Reality and Liberation Praxis from Ignacio Ellacuría (Andamios, Revista de Investigación Social, 2024)
The present paper offers an approach to the mature thought of Ignacio Ellacuría Beascoechea (1930-1989), focusing on the fundamental categories of historical reality and praxis, and highlighting the importance of integrating different disciplinary perspectives in order to understand reality and overcome ideologization. In this sense, focusing on the relationship between philosophy and theology, it is proposed that Ellacuría resolves the conflict of disciplinary hierarchization and emphasizes the need for a methodological and epistemological balance that allows enriching the concepts and promoting a dialogue with implications in the transformation of society that overcomes the depletion of different knowledges and promotes an ecology of knowledge.
Keywords: Historical reality; praxis; liberation; transdisciplinarity